The Regeneration of Large-Sized and Vascularized Adipose Tissue Using a Tailored Elastic Scaffold and dECM Hydrogels - Kim, Su Hee; Kim, Donghak; Cha, Misun; Kim, Soo Hyun; Jung, Youngmee (MDPI, 2021)
A dome-shaped elastic poly(l-lactide-co-caprolactone) (PLCL) scaffold with a channel and pore structure was fabricated by a combinative method of 3D printing technology and the gel pressing method (13 mm in diameter and 6.5 mm in thickness) for patient-specific regeneration. The PLCL scaffold was combined with adipose decellularized extracellular matrix (adECM) and heart decellularized extracellular matrix (hdECM) hydrogels and human adipose-derived stem cells (hADSCs) to promote adipogenesis and angiogenesis. These scaffolds had mechanical properties similar to those of native adipose tissue for improved tissue regeneration. The results of the in vitro real-time PCR showed that the dECM hydrogel mixture induces adipogenesis. In addition, the in vivo study at 12 weeks demonstrated that the tissue-engineered PLCL scaffolds containing the hydrogel mixture (hdECM/adECM (80:20)) and hADSCs promoted angiogenesis and adipose tissue formation, and suppressed apoptosis. Therefore, we expect that our constructs will be clinically applicable as material for the regeneration of patient-specific large-sized adipose tissue.
Keywords: ANGIOGENESIS; RECONSTRUCTION; DELIVERY; SYSTEM; BREAST; FUTURE